Boosting dual-interfacial polarization by decorating hydrophobic graphene with high-crystalline core-shell FeCo@Fe3O4 nanoparticle for improved microwave absorption. (January 2022) - Sun, Yong; Zhou, Bo; Wang, Hongpeng; Deng, Xia; Feng, Juan; He, Mi; Li, Xinghua; Zhu, Xiuhong; Peng, Yong; Zheng, Xinliang
Abstract: Manufacturing heterostructure architectures with multiple interfaces and understanding the interfacial polarizations are important for exploring high-efficient microwave absorbents. Herein, high-crystalline core-shell FeCo@Fe3 O4 nanoparticles were in-situ anchored on graphene. The FeCo@Fe3 O4 /graphene hybrids reveal boosting microwave absorption which can be adjusted by controlling the graphene component. The hybrids show an optimal reflection loss of −74.4 dB at 9.6 GHz with a thickness of 2.58 mm. The effective absorption bandwidth can reach 3.7–18 GHz when the thickness is 1.5–5.0 mm. The improved microwave absorption is attributed to better impedance matching, high attenuation capacity and boosting dielectric polarization. The specific heterostructures comprised of FeCo core, Fe3 O4 shell and graphene nanosheet carrier can induce abundant multiple heterogeneous interfaces, which can generate lattice distortion for dipolar polarization and introduce space charge separation for interface polarization. Theoretical calculation demonstrates that electrons transfer among the multiple interfaces and generate charge redistribution, leading to dipole and interface polarizations. Besides, the hybrids are hydrophobic, which can improve the stability of electric devices in wet. This work not only provides a point of view to boost the microwave absorption through dielectric polarization, but also gives a new insight to design environmentally friendly microwave absorbents by hydrophobic treatment. Graphical abstract: Image 1 Highlights: Crystalline core-shell FeCo@Fe3 O4 /graphene was designed as microwave absorbent. The heterogeneous structure induces interfacial polarizations for boosting microwave absorption. The hybrids show an optimal RL of −74.4 dB at 9.6 GHz with a thickness of 2.58 mm. The hybrids show hydrophobic feature, enhancing the stability and service life in wet environment.